CATALYTIC REFORMING OF HEAVY NAPHTHA, ANALYSIS AND SIMULATION - Zaidoon M. Shakoor (Diyala Journal of Engineering Sciences, 2011)
In this paper, one-dimensional steady-state mathematical model of a semi regenerative naphtha catalytic reforming process had been made. This model incorporated a detailed kinetic model involving 24 components, 1 to 11 carbon atoms for paraffins (n and iso) and 6 to 11 carbon atom for naphthenes and aromatics with 71 reactions. The effect of pressure drop was considered through Ergun equation. The model explains the composition, temperature and pressure distributions along the four reforming reactors.